2013
DOI: 10.1002/mnfr.201200594
|View full text |Cite
|
Sign up to set email alerts
|

Major phenylpropanoid‐derived metabolites in the human gut can arise from microbial fermentation of protein

Abstract: This study demonstrates that certain microbial species have the ability to ferment all three AAAs and that protein fermentation is the likely source of major phenylpropanoid-derived metabolites in the colon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
251
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 320 publications
(262 citation statements)
references
References 37 publications
8
251
0
3
Order By: Relevance
“…This supports the hypothesis that Bifidobacterium spp. regulate the growth of bacterial species with high enzymatic capacities to produce IS and PCS (27), such as bacteria from the Clostridales order and Ruminococcaceae family, which both decreased after synbiotics (28,29). The findings support those of a recent study that showed that consumption of Bifidobacterium-fermented milk and GOS reduced serum phenols in healthy adult women (30).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This supports the hypothesis that Bifidobacterium spp. regulate the growth of bacterial species with high enzymatic capacities to produce IS and PCS (27), such as bacteria from the Clostridales order and Ruminococcaceae family, which both decreased after synbiotics (28,29). The findings support those of a recent study that showed that consumption of Bifidobacterium-fermented milk and GOS reduced serum phenols in healthy adult women (30).…”
Section: Discussionsupporting
confidence: 85%
“…Lastly, the analysis of the stool microbiome may not have reflected alterations in the mucosalassociated microbiomes within the large and small bowel. Furthermore, despite recent studies inferring functional attributes of these microbial communities by comparison with reference microbial genomes (29), such an approach cannot readily account for variations in gene expression, which are influenced by the colonic environment (e.g., pH and carbohydrate availability) (28).…”
Section: Discussionmentioning
confidence: 99%
“…However, we could not identify the p-aminobenzoic acid biosynthesis pathway in the genome (see Table S2 in the supplemental material), in line with previous results that F. prausnitzii M21/2 does not possess the complete folate biosynthesis pathway (40). Finally, F. prausnitzii secreted five previously unreported metabolites (see Table S2 in the supplemental material), namely, dihydroorotic acid, N-acetylglutamic acid, N-acetylaspartic acid, and 3-methy2-oxovaleric acid, as well as phenyllactic acid, which has already been shown to be produced by F. prausnitzii strains M21/2 and SL3/3 (41).…”
Section: Figmentioning
confidence: 65%
“…32 We predicted the production of aromatic amino acid-derived phenolic metabolites by gut microbes (Table S4), which is supported by experimental data and may have implications for vascular health. 23 In our model, cadaverine was only produced by the 5 Gammaproteobacteria (Table S4). This compound is elevated in the fecal extracts of ulcerative colitis (UC) patients.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the well-described microbial production of a variety of phenolic compounds from aromatic amino acids 23 was predicted (Table S4). Other modeled products derived from amino acids included sulfide and ammonia, which are toxic and disturb colonocyte energy metabolism.…”
Section: Luminal Secretionmentioning
confidence: 99%